Detection and parameter estimation of signals in parallel processing systems - Литвин-Попович, А.И. (Radiotekhnika, 2012)
Problem of signal detection has been discussed with an emphasis on a situation when some signal parameters are not known a priori. This problem can be solved with a multi-channel correlator or a filter receiver. Question of estimation of an a priori unknown signal parameter have been discussed. Usage of parallel computing devices – multicore universal and graphical processors (GPU) – makes it possible to create such receiver with a high number of parallel channels while sustaining required rate of results.